2017
DOI: 10.1039/c6gc03604j
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated polyaniline as a solid organocatalyst for dehydration of fructose into 5-hydroxymethylfurfural

Abstract: Sulfonated polyaniline with mutually reactive sulfonic acid groups and amine/imine represents an organocatalyst for effective production of 5-hydroxymethylfurfural (HMF) from carbohydrates in low-boiling solvents with complete restriction of HMF rehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Despite a number of examples demonstrating the successful conversion of fructose into HMF, most of them do not meet practical requirements, due to the high cost of the refined input carbohydrate substrates (mostly, fructose and sucrose). If naturally abundant glucose or polyglucosides can be converted selectively into HMF in high yields, the process could become industrially viable and so the high‐yielding conversion of glucose into fructose is desirable.…”
Section: Conversion Of Carbohydrates In Water and Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a number of examples demonstrating the successful conversion of fructose into HMF, most of them do not meet practical requirements, due to the high cost of the refined input carbohydrate substrates (mostly, fructose and sucrose). If naturally abundant glucose or polyglucosides can be converted selectively into HMF in high yields, the process could become industrially viable and so the high‐yielding conversion of glucose into fructose is desirable.…”
Section: Conversion Of Carbohydrates In Water and Organic Solventsmentioning
confidence: 99%
“…), which additionally support the dehydration of fructose. [64][65][66] Despite an umber of examples demonstrating the successful conversion of fructosei nto HMF, [28,33,34,[67][68][69] most of them do not meet practical requirements,d ue to the high cost of the refined input carbohydrate substrates (mostly,f ructosea nd sucrose). If naturally abundant glucoseo rp olyglucosides can be converted selectively into HMF in high yields, the process Scheme2.Proposed mechanism for Lewis acid catalyzed glucose-fructose isomerization.…”
Section: Hmf and Its Derivativesmentioning
confidence: 99%
“…Common solid acid catalysts include carbon-based solid acids, molecular sieves, ion-exchange resins, and heteropoly acids [71]. Degradation of monosaccharide, starch, cellulose, and other biomasses to HMF using solid acid catalysts has been investigated ( Table 2) [72][73][74][75][76], but degradation of chitin biomass using solid acid catalysts has rarely been reported. Kalane et al [77] combined a solid acid catalyst with different concentrations of acetic acid to catalyze chitosan conversion to HMF by "green" synthesis.…”
Section: Hmf Production From Chitin Biomass By Lewis Acidsmentioning
confidence: 99%
“…Notably, polyaniline (PAN) has recently received particular interest in catalytic applications as a heterogeneous organic support owing to its facile synthesis, air-stable performance, good dispersion of active species, and the pseudo-homogeneous character in organic solvents [20,[37][38][39][40][41][42][43][44]. In our group, we found that the functionalized PANs exhibited promising catalytic performance towards the dehydration of fructose into furans [45][46][47]. Considering the advantages and characteristics of PAN, we are expecting to incorporate the Mo-involved redox sites into the PAN "supports" such that the bifunctions of oxidation and dehydration could be combined, and even strengthened in a single inorganic-organic hybrid catalyst.…”
Section: Introductionmentioning
confidence: 97%